Revolutionizing Healthcare with AI: Innovative Strategies in Cancer Medicine - Murad Khan; Ashish Shiwlani; Muhammad Umer Qayyum; Abdul Mannan Khan Sherani; Hafiz Khawar Hussain (International Journal of Multidisciplinary Sciences and Arts, 2024)
By improving early detection, diagnosis, treatment planning, and patient management, artificial intelligence (AI) is transforming the way that cancer is treated. An overview of AI's function in cancer is given in this article, with special attention to how it advances precision medicine and improves patient outcomes. Numerous AI applications are discussed, such as predictive analytics, pathology interpretation, genetic profiling, and medical imaging analysis. Case studies highlight effective AI applications in cancer care, showcasing the technology's effectiveness in enhancing the precision of diagnoses, directing individualized treatment choices, and tracking treatment response. The paper delves into the possible advancements in early identification, therapy optimization, and patient engagement through an exploration of future directions and innovations in AI-driven oncology research. The conclusion emphasizes how AI has the ability to completely change the way cancer is treated and enhance the lives of cancer sufferers all over the world.